2011
DOI: 10.4314/acsj.v18i4.68645
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and physiological aspects related to drought tolerance in sorghum

Abstract: Drought is one of the major limitations to crop productivity worldwide. Identifying suitable screening tools and quantifiable traits would facilitate the crop improvement process for drought tolerance in sorghum. This study evaluated phenotypic characteristics and physiological parameters determine which cultivars are more drought tolerant. Signs of drought intolerance in sorghum include leaf rolling, death of lower leaves, stunted growth and low yields. Experiments were conducted using 8 and 25 sorghum access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Global climate change has increased the incidence of drought worldwide across successive years (Shanker et al, 2014 ), and it has had many negative effects on plant growth such as leaf rolling, growth inhibition, and death (Mutisya et al, 2010 ), thus severely affecting agriculture. Sudan grass ( Sorghum sudanense ) is an annual warm-season gramineous forage grass (Smith et al, 1982 ; Zhan et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change has increased the incidence of drought worldwide across successive years (Shanker et al, 2014 ), and it has had many negative effects on plant growth such as leaf rolling, growth inhibition, and death (Mutisya et al, 2010 ), thus severely affecting agriculture. Sudan grass ( Sorghum sudanense ) is an annual warm-season gramineous forage grass (Smith et al, 1982 ; Zhan et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lower stomatal conductance has been shown to result in higher TE and greater accumulation of biomass in crops (Xin et al 2009). Mutisya et al (2010) reported that high RWC was correlated to drought tolerance in sorghum. Water deficit stress that determines the grain yield is known to alter many physiological processes such as leaf temperature, stomatal conductance, transpiration, photosynthesis and respiration (Mutisya et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the present study, grain yield was strongly correlated to number of roots/plant under stress at GS2 and control conditions. Greater numbers of roots give increased accessibility to moisture and nutrients (Patil & Biradar 2005); it has been found that drought-tolerant lines show the highest root length and weight (Mutisya et al 2010). The root traits (root length, root dry weight and root number) play important roles in overcoming moisture stress in sorghum (Maiti 1996).…”
Section: Discussionmentioning
confidence: 99%